New correlations for the prediction of the undisturbed ground temperature. (January 2015) - Ouzzane, Mohamed; Eslami-Nejad, Parham; Badache, Messaoud; Aidoun, Zine
Highlights: Correlation for the undisturbed ground temperature has been developed. The ambient temperature includes the effect of solar and convection fluxes. The undisturbed ground temperature is used for geothermal heat pump design. The undisturbed ground temperature map for Canada has been generated. Abstract: The undisturbed ground temperature is an important parameter in the design of the ground heat exchanger connected to the ground source heat pump systems. Based on the heating mode for cold climates, the underestimation of this parameter leads to oversizing the ground heat exchanger length and therefore resulting in the additional cost of the system. Using measured data obtained from thermal response test (TRT) reports for seventeen sites covering a wide range of climates, two different correlations of the undisturbed ground temperature, global and simplified have been developed. The first one, obtained using the least square method, is a function of ambient air temperature, wind velocity, global solar radiation on a horizontal surface and sky temperature. It has been shown by using this correlation that the air ambient temperature is the dominant parameter on the undisturbed ground temperature. Following this conclusion, the simplified correlation which is only a function of the air ambient temperature was developed. Then using this latter correlation, isotherms of the undisturbed ground temperature for Canada were generated.